Pregnancy, Viral Infection, and COVID-19 - Alberca, Ricardo Wesley; Pereira, Nátalli Zanete; Oliveira, Luanda Mara Da Silva; Gozzi-Silva, Sarah Cristina; Sato, Maria Notomi (Frontiers in Immunology, 2020)
Pregnancy comprises a unique immunological condition, to allow fetal development and to protect the host from pathogenic infections. Viral infections during pregnancy can disrupt immunological tolerance and may generate deleterious effects on the fetus. Despite these possible links between pregnancy and infection-induced morbidity, it is unclear how pregnancy interferes with maternal response to some viral pathogens. In this context, the novel coronavirus (SARS-CoV-2) can induce the coronavirus diseases -2019 (COVID-19) in pregnant women. The potential risk of vertical transmission is unclear, babies born from COVID-19-positive mothers seems to have no serious clinical symptoms, the possible mechanisms are discussed, which highlights that checking the children’s outcome and more research is warranted. In this review, we investigate the reports concerning viral infections and COVID-19 during pregnancy, to establish a correlation and possible implications of COVID-19 during pregnancy and neonatal´s health.